2015
DOI: 10.1037/apl0000021
|View full text |Cite
|
Sign up to set email alerts
|

Mental skills training with basic combat training soldiers: A group-randomized trial.

Abstract: Cognitive skills training has been linked to greater skills, self-efficacy, and performance. Although research in a variety of organizational settings has demonstrated training efficacy, few studies have assessed cognitive skills training using rigorous, longitudinal, randomized trials with active controls. The present study examined cognitive skills training in a high-risk occupation by randomizing 48 platoons (N = 2,432 soldiers) in basic combat training to either (a) mental skills training or (b) an active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 51 publications
3
59
0
1
Order By: Relevance
“…HPWSs are likely to send positive signals to employees that their organisation regards their contributions as important and is concerned about their well‐being. For example, extensive training enhances employees' knowledge, skills, and abilities and is linked to greater skills, self‐efficacy, and performance (Adler et al, ); thus, such training is perceived as a signal that employees are respected and valued and that their development is taken seriously (Shore & Shore, ). Promotions, performance evaluations, and rewards with a focus on performance are used by employers to motivate individuals to contribute to organisational competitive advantage, to acknowledge and express appreciation for their accomplishments, and to demonstrate that they care about employee well‐being (DeNisi & Murphy, ; Liao et al, ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…HPWSs are likely to send positive signals to employees that their organisation regards their contributions as important and is concerned about their well‐being. For example, extensive training enhances employees' knowledge, skills, and abilities and is linked to greater skills, self‐efficacy, and performance (Adler et al, ); thus, such training is perceived as a signal that employees are respected and valued and that their development is taken seriously (Shore & Shore, ). Promotions, performance evaluations, and rewards with a focus on performance are used by employers to motivate individuals to contribute to organisational competitive advantage, to acknowledge and express appreciation for their accomplishments, and to demonstrate that they care about employee well‐being (DeNisi & Murphy, ; Liao et al, ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Furthermore, many sports events have evolved from military tasks such as: marksmanship (e.g., rifle shooting, archery), overcoming physical obstacles or defences (e.g., pole vault, high jump and cross country running), and navigation (e.g., orienteering, sailing; Goodwin, 2008). Given the similarities between sport and military performance, the application of sport psychology in the military is increasingly being recognized (e.g., Adler et al, 2015).…”
mentioning
confidence: 99%
“…Over the past 40 years, numerous studies have demonstrated that psychological skills (PS) benefit athlete well-being and performance (e.g., Hayslip, Petrie, MacIntyre, & Jones, 2010;Thelwell & Greenlees, 2003) and initial research has linked PS training and military performance (Hammermeister, Pickering, McGraw, & Ohlson, 2010). One recent longitudinal experiment (Adler et al, 2015) revealed improvements in self-confidence and performance on a 20m aerial obstacle task for soldiers completing PS training in comparison to soldiers in an active control condition. However, it remains unclear exactly how such effects emerged.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These attitudes re ect the ability to use coping skills (53) that place challenges into perspective and that re ect the importance of nding meaning in one's life and work. Skills related to these concepts could be strengthened in service members directly through training (53,54), and indirectly through institutional messaging about the importance of positive perspective and selfmastery, and through leaders who set an example and reinforce these attitudes. By supporting these kinds of adaptive skills and perceptions, studies could examine whether the risk of problematic anger years later may be lowered.…”
Section: Discussionmentioning
confidence: 99%